Microglial infiltration mediates cognitive dysfunction in rat models of hypothalamic obesity via a hypothalamic-hippocampal circuit involving the lateral hypothalamic area - Song, Chong; Wei, Wei; Wang, Tong; Zhou, Min; Li, Yunshi; Xiao, Bing; Huang, Dongyi; Gu, Junwei; Shi, Linyong; Peng, Junjie; Jin, Dianshi (Frontiers in Cellular Neuroscience, 2022)
This study aimed to explore the mechanism underlying cognitive dysfunction mediated by the lateral hypothalamic area (LHA) in a hypothalamic-hippocampal circuit in rats with lesion-induced hypothalamic obesity (HO). The HO model was established by electrically lesioning the hypothalamic nuclei. The open field (OP) test, Morris water maze (MWM), novel object recognition (NOR) and novel object location memory (NLM) tests were used to evaluate changes in cognition due to alterations in the hypothalamic-hippocampal circuit. Western blotting, immunohistochemical staining, and cholera toxin subunit B conjugated with Alexa Fluor 488 (CTB488) reverse tracer technology were used to determine synaptophysin (SYN), postsynaptic density protein 95 (PSD95), ionized calcium binding adaptor molecule 1 (Iba1), neuronal nuclear protein (NeuN) and Caspase3 expression levels and the hypothalamic-hippocampal circuit. In HO rats, severe obesity was associated with cognitive dysfunction after the lesion of the hypothalamus. Furthermore, neuronal apoptosis and activated microglia in the downstream of the lesion area (the LHA) induced microglial infiltration into the intact hippocampus via the LHA-hippocampal circuit, and the synapses engulfment in the hippocampus may be the underlying mechanism by which the remodeled microglial mediates memory impairments in HO rats. The HO rats exhibited microglial infiltration and synapse loss into the hippocampus from the lesioned LHA via the hypothalamic-hippocampal circuit. The underlying mechanisms of memory function may be related to the circuit.